2018
DOI: 10.1097/01.asw.0000540069.99416.a6
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring and Molecular Characterization of Staphylococcus aureus Isolated from Chronic Wounds

Abstract: Compared with those colonized by MSSA, chronic wounds colonized by MRSA did not display a strong correlation with the presence of a greater number of clinical signs of infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
0
5
0
3
Order By: Relevance
“…In a study carried out in the same scenario, Staphylococcus aureus was detected in 71.4% (25/35) of the wounds in samples collected by swab, 2 patients had Methicillin-resistant Staphylococcus aureus (MRSA); however, according to the clinical criteria, 8 (22.9%) patients presented signs of infection in their wounds. Wounds colonized with MRSA did not show a strong correlation with the presence of a greater number of clinical signs of infection 20 . Most of the wounds are colonized by bacteria, while only a few have clinically relevant wound infection characteristics 21 .…”
Section: Discussionmentioning
confidence: 82%
“…In a study carried out in the same scenario, Staphylococcus aureus was detected in 71.4% (25/35) of the wounds in samples collected by swab, 2 patients had Methicillin-resistant Staphylococcus aureus (MRSA); however, according to the clinical criteria, 8 (22.9%) patients presented signs of infection in their wounds. Wounds colonized with MRSA did not show a strong correlation with the presence of a greater number of clinical signs of infection 20 . Most of the wounds are colonized by bacteria, while only a few have clinically relevant wound infection characteristics 21 .…”
Section: Discussionmentioning
confidence: 82%
“…The identification of MRSA strains among patients from this study who were under ambulatory follow‐up care at a health unit located within a large hospital complex indicates a need to implement precautionary measures of contact in outpatient clinics to minimise the risks of cross‐contamination by multidrug‐resistant microorganisms. The results of previous studies indicated the non‐occurrence of this type of contamination in the units where this study was performed . However, periodic reassessments are warranted because selection pressure to generate multidrug‐resistant microorganisms increases proportionately with time and as the use of new commercially available antimicrobials increases.…”
Section: Discussionmentioning
confidence: 83%
“…Em estudo realizado no mesmo cenário, Staphylococcus aureus foi detectado em 71,4% (25/35) das feridas em amostras coletadas por swab, 2 pacientes tinham Staphylococcus aureus resistente à meticilina (MRSA), entretanto, de acordo com os critérios clínicos, 8 (22,9%) pacientes apresentaram sinal de infecção em suas feridas. As feridas colonizadas por MRSA não mostraram uma forte correlação com a presença de um maior número de sinais clínicos de infecção 20 . A maioria das feridas é colonizada por bactérias, enquanto apenas algumas têm características de infecção de ferida clinicamente relevante 21 .…”
Section: Discussionunclassified